Exon skipping and gene transfer restore dystrophin expression in human induced pluripotent stem cells-cardiomyocytes harboring DMD mutations - Dick, Emily; Kalra, Spandan; Anderson, David; George, Vinoj; Ritso, Morten; Laval, Steven H.; Barresi, Rita; Asrtsma-Rus, Annemieke; Lochmueller, Hanns; Denning, Chris (Mary Ann Liebert, 2013)
With an incidence of 1:3,500 to 5,000 in male children, Duchenne muscular dystrophy (DMD) is an X-linked disorder in which progressive muscle degeneration occurs and affected boys usually die in their twenties or thirties. Cardiac involvement occurs in 90% of patients and heart failure accounts for up to 40% of deaths. To enable new therapeutics such as gene therapy and exon skipping to be tested in human cardiomyocytes, we produced human induced pluripotent stem cells (hiPSC) from seven patients harboring mutations across the DMD gene. Mutations were retained during differentiation and analysis indicated the cardiomyocytes showed a dystrophic gene expression profile. Antisense oligonucleotide-mediated skipping of exon 51 restored dystrophin expression to 30% of normal levels in hiPSC-cardiomyocytes carrying exon 47–50 or 48–50 deletions. Alternatively, delivery of a dystrophin minigene to cardiomyocytes with a deletion in exon 35 or a point mutation in exon 70 allowed expression levels similar to those seen in healthy cells. This demonstrates that DMD hiPSC-cardiomyocytes provide a novel tool to evaluate whether new therapeutics can restore dystrophin expression in the heart.